A comparison study on phase transition and structure of cornstarch in dimethyl sulfoxide and ionic liquid systems. (September 2016) - Zhang, Shaobo; Wang, Chunyan; Fu, Xiong; Liu, Hongsheng; Yu, Long; Qiao, Qian; Jiang, Tianyu
Abstract: A comparison study of the phase transition and structure of waxy cornstarch in DMSO and AMIMCl systems was conducted using a differential scanning calorimeter, an optical microscope, a scanning electron microscope, X-ray diffraction and thermogravimetric analysis. A full disruption and dissolution of starch granules was completed in 10 h at room temperature in pure DMSO, which was faster and more effective than that in ionic liquid 1-allyl-3-methylimidazolium chloride (AMIMCl). When dispersed in DMSO/water and AMIMCl/water at various ratios, respectively, different phase transitions were clearly exhibited, and the appearance and crystal structure of starch granules were significantly damaged with an increase in the concentration. Basing on the study of the decomposition temperature change through TGA measurements, a decreased temperature was observed in both DMSO and AMIMCl system, meaning starch degradation occurred with different levels. The huge temperature change from 357 to 328 °C were found in AMIMCl system, which most likely induced the distinct exothermic phenomenon in the DSC observation due to a significant depolymerization of starch. Highlights: IOD method was applied to compare starch dissolution in DMSO and AMIMCl system. A disruption and dissolution of starch in DMSO was completed in 10 h, which was faster than those in IL. Thermal enthalpy ( △H) of starch gelatinization was gradually reduced with increasing DMSO concentration. Starch degradation occurred with different levels in DMSO and AMIMCl system. No exothermic phenomenon was observed in pure DMSO due to a slight degradation of starch.